Impact of smartphone overuse on 1-year severe depressive symptoms and momentary negative affect: Longitudinal and experience sampling findings from a representative epidemiological youth sample in Hong Kong. (December 2022) - Wong, Stephanie MY; Chen, Eric YH; Wong, Corine SM; Suen, YN; Chan, Dorothy LK; Tsang, Samantha HS; Wong, TY; Cheung, Charlton; Chan, KT; Lui, Simon SY; Wong, Michael TH; Chan, Sherry KW; et al.
Highlights: Smartphone overuse is present in 29.3% of the youth population in Hong Kong. Smartphone overuse is prospectively associated with severe depressive symptoms and poorer functioning at 1 year. Smartphone overuse is also associated with elevated momentary negative affect, even when accounting for baseline depressive symptoms. Depressive symptoms, in contrast, were not significant for 1-year smartphone overuse when adjusting for baseline smartphone overuse. Mitigating the impact of smartphone overuse can have important long-term implications for youth mental health. Abstract: Smartphone overuse can have detrimental impacts on youth mental health. How it may be longitudinally associated with depressive symptoms and functioning, and with daily momentary affect, remains to be investigated. A total of 3, 033 young people were consecutively recruited from a large-scale epidemiological youth mental health study in Hong Kong. A subsample ( n  = 936) was followed-up after 1 year, with experience sampling data collected from 177 participants. Separate multivariable logistic regression models were applied to examine the prospective associations between smartphone overuse and depressive symptoms, with multilevel models fitted to examine its associations with momentary affect. The prevalence of smartphone overuse in the Hong Kong youth population was 29.3%. Smartphone overuse was significantly associated with more depressive symptoms and functional impairments both cross-sectionally and longitudinally. The associations between smartphone overuse and 1-year depressive symptoms were significant, even when accounting for baseline symptoms, social media use, and other risk and protective factors. Baseline depressive symptoms, in contrast, were not associated with 1-year smartphone overuse after adjusting for baseline smartphone overuse. Smartphone overuse was also significantly associated with higher levels of momentary negative affect, even when accounting for depressive symptoms. Strategies to mitigate the impact of smartphone overuse can have important long-term implications.